Influence of carbon nanotubes on the performance of bismuth sodium titanate-bismuth potassium titanate-barium titanate ceramic/cement composites - Ruamporn Potong (2018)
© 2017 Elsevier Ltd and Techna Group S.r.l. Lead-free bismuth sodium titanate-bismuth potassium titanate-barium titanate ceramic/cement composites with carbon nanotubes (CNTs) addition were developed for smart structures application. The pores in composite and insulating nature of the cement matrix made the poling difficult and lower piezoelectric activities of composites. In this work, CNTs additions as a conducting phase at 0–2% by volume was mixed with ceramic and Portland cement by pressing and curing method. The influence and optimum of CNTs content on the microstructure, dielectric, electrical conductivity, acoustic impedance and piezoelectric properties of composites were studied. The results indicate that the CNTs are filled in the pores between the hydration products of cement as observed using scanning electron microscope. The highest piezoelectric coefficient (d 33 ) and piezoelectric voltage coefficient (g 33 ) values of composite with CNTs content was found at 1% by volume where the values are 58 pC/N and 30.20 × 10 −3 Vm/N, respectively. Therefore, CNTs content at 1% by volume was optimum for improvement of the piezoelectric properties for cement based-ceramic composites. All composites with CNTs content in the range tested were found to have good compatibility with concrete structure with matching acoustic properties.